WEB-BASED SCHOOL INFORMATION SYSTEM (CASE STUDY OF PRIVATE HIGH SCHOOL PGRI 1 KOTABUMI LAMPUNG UTARA) - Pratama, Iqnatian Aidil; Afandi, Asep; Efendi, Dwi Marisa (Institut Bakti Nusantara, 2024)
The process of conveying information that is currently running, often encounters obstacles, administrative staff at SMAS PGRI 1 Kotabumi often experience difficulties, such as difficulties in the process of delivering information to students and the public. Other impacts of the current system are administrative staff often experience data loss. because the data storage media still uses ledgers and computer hard disks. Thus a web-based school information system was built at SMAS PGRI using the extrame programming method which can be used as a medium for conveying information to students and teachers. Based on the school information system trial, it produces an information system that can be used to convey information between the school and students and teachers